Financial Protection of the State against Natural Disasters : A Primer - Ghesquiere, Francis (2012)
This paper has been prepared for policy makers interested in establishing or strengthening financial strategies to increase the financial response capacity of governments of developing countries in the aftermath of natural disasters, while protecting their long-term fiscal balances. It analyzes various aspects of emergency financing, including the types of instruments available, their relative costs and disbursement speeds, and how these can be combined to provide cost-effective financing for the different phases that follow a disaster. The paper explains why governments are usually better served by retaining most of their natural disaster risk while using risk transfer mechanisms to manage the excess volatility of their budgets or access immediate liquidity after a disaster. Finally, it discusses innovative approaches to disaster risk financing and provides examples of strategies that developing countries have implemented in recent years.